Tuberculum meningioma – Deﬁning those ideal for endoscopic extended endonasal approach - Lawrence, Alistair; Nair, Ramesh (Journal of Neurosurgery Academy, 2025)
This study evaluates the endoscopic extended endonasal approach (EEA) for tuberculum sellae meningiomas, emphasizing key anatomical factors for optimal patient selection. The EEA offers direct tumor access with minimal neural manipulation, facilitating complete resection in suitable cases. Limitations include tumors extending beyond the medial optico-carotid recess or encasing vascular structures. Careful preoperative assessment can maximize resection success and minimize complications. A video demonstration of an ideal case is included.